Juridical Analysis of Intermediary Criminal Acts in Ecstasy Transactions: A Study of Dumai District Court Decision Number 188/Pid.Sus/2025/PN Dum - Purba, Josua Sotarduga; Risdalina, Risdalina; Kusno, Kusno (CV. Social Politic Genius (SIGn), 2025)
Law enforcement in narcotics offenses frequently encounters a clash between the legal certainty of proving the elements of the offense and substantive justice in imposing criminal sanctions on subordinate intermediary offenders. Decision Number 188/Pid.Sus/2025/PN Dum imposed a six-year imprisonment and a fine of one billion rupiah on the Defendant. This research aims to examine the accuracy of the Panel of Judges’ legal qualification in applying the elements of an intermediary in narcotics transactions and to critically analyze the proportionality of criminal sanctions based on the offender’s degree of culpability. This normative legal research utilizes the statute approach and the case approach, employing an analytical-prescriptive analysis technique through a legal syllogism. The results indicate that the Panel of Judges absolutely and accurately applied the substantive law of Article 114 section (1) of Law Number 35 of 2009 by considering the defendant’s active initiative in facilitating the transaction. In the sentencing dimension, the decision was proportionate and objective. The Panel of Judges did not merely take refuge behind the minimum sanction limits, but comprehensively differentiated roles by rejecting the narrative of sociological excusability regarding the defendant’s factual position as a field operator. In conclusion, the conviction is normatively valid and successfully presents substantive justice grounded in the individual’s degree of culpability. As a policy implication, the Supreme Court is recommended to immediately formulate sentencing guidelines for narcotics offenses that are hierarchically binding to maintain the consistency of high-quality legal reasoning across all judicial levels.